The Importance of Teaching the Literary Analysis of Idea, Characters, Plot Summary of the Story “Escape” by Somerset Maugham - kizi, Gavharoy Isroiljon; Maxsumaxon, Odiljonova (European Journal of Life Safety and Stability (2660-9630), 2021)
In this article is given more imformation about the importance of teaching the literary analysis of idea, characters, plot summary of the story “Escape” by Somerset Maugham. Somerset Maugham English novelist, playwright, and short-story writer whose work is characterized by an unique understanding of human nature. If we were, the foreign language teachers, can provide or create a life-like situation in which our students are exposed to adequate foreign language inputs, and motivated the students to use the foreign language while teaching them the language concepts, the students will greatly improve their communicative competence.